Pengaruh Kompensasi, Keselamatan Kerja, Kesehatan Kerja Karyawan Perusahaan Paralon - Rizkillah, Anggilia Dwi; Aslamiyah, Suaibatul; Wati, Hernum Daya (Jurnal Mahasiswa Manajemen, 2024)
Background : The current economic uncertainty also impacts business stability. Amid these pressures, the rise in workplace accidents and decline in employee performance highlight the importance of improving compensation, workplace safety, and health programs to maintain employee well-being and productivity. Objective : This study is to ascertain how paralon company employees' performance is affected by compensation, workplace safety, and occupational health. Design / Methodology / Approach : Multiple linear regression analysis is the research technique employed. To guarantee the accuracy and dependability of the data and model, testing methods such as validity, reliability, normality, multicollinearity, heteroscedasticity, and hypothesis tests were used. Findings : The study results indicate that compensation, workplace safety, and occupational health variables have a significant effect on employee performance. Validity and reliability tests confirmed that the research instruments are valid and reliable. The normality test showed that the data distribution is normal, while multicollinearity and heteroscedasticity tests indicate no major issues in the regression model. The coefficient of determination shows that the three independent variables can explain 91.9% of the variation in employee performance. Research Implication : The results of this study indicate that the three variables have a significant impact on employee performance. Therefore, companies should prioritize these three aspects to improve employee performance. Limitation : This study only examines three independent variables (compensation, occupational safety, and occupational health), therefore the results may not fully explain the factors that influence employee performance